Closed work - a site for an open world: o lugar para um mundo aberto - Romãozinho, Ana (Farol, 2023)
This article analyzes the series “ludografia”, created from a pre-established rule for the development of each work belonging to the series. In view of the approach to the pre-established limit, it is intended to analyze the influences that the restrictions of the COVID-19 pandemic had on the possible link between the imposition of rules and the creative process, referring to the idea of ​​a game and inviting reflections on the roles and different relationships that may arise between the proposer (the artist) and the audience (the one who plays).
Keywords: game; limit; rule; ludography